Evaluating the impact of motion artifact on noninvasive blood pressure devices. Issue 4 (5th April 2020) - Alpert, Bruce S.; Quinn, David E.; Friedman, Bruce C.; Matsumura, Paul M.; Dart, Richard A.; Donehoo, Robert F.
Abstract: Most automated sphygmomanometers use oscillometric algorithms. Motion, either patient‐based or environmental, will affect the ability of a device to record an accurate blood pressure (BP). Members of the Association for the Advancement of Medical Instrumentation (AAMI) Sphygmomanometer Committee have been studying this problem for more than a decade. The AAMI TIR44 was the first publication to address the challenges of motion tolerance. The concepts described in TIR44 have led to the development of a draft of ISO 81060‐4, a new standard for testing devices for which the manufacturer wishes to claim motion tolerance. The current ISO 81060‐2 addresses both stress testing and 24‐hour ambulatory BP monitoring. Recent publications have reported on testing of devices in response to voluntary and involuntary patient motion. The ISO 81060‐4 will address testing in the presence of patient transport by ground, fixed‐wing, and rotary (helicopter) ambulances. The protocol will utilize noise profiles recorded under those three conditions. The profiles will be digitally stored on a library with free access. The proposed testing will be performed using patient simulators introducing the noise library files into known BP oscillometric envelopes. The specifications of the data capture and playback devices are specified, as is the evaluation statistical testing. The authors expect that the final draft will be published in 2020.